Use of Ultrasmall Superparamagnetic Iron Oxide Enhanced Susceptibility Weighted Imaging and Mean Vessel Density Imaging to Monitor Antiangiogenic Effects of Sorafenib on Experimental Hepatocellular Carcinoma. (21st June 2017) - Yang, Shuohui; Lin, Jiang; Lu, Fang; Han, Zhihong; Fu, Caixia; Gu, Hongchen
Abstract : We investigated effectiveness of ultrasmall superparamagnetic iron oxide enhanced susceptibility weighted imaging (USPIO-enhanced SWI) and mean vessel density imaging ( Q ) in monitoring antiangiogenic effects of Sorafenib on orthotopic hepatocellular carcinoma (HCC). Thirty-five HCC xenografts were established. USPIO-enhanced SWI and Q were performed on a 1.5 T MR scanner at baseline, 7, 14, and 21 days after Sorafenib treatment. Intratumoral susceptibility signal intensity (ITSS) and Q were serially measured and compared between the treated ( n = 15) and control groups ( n = 15). Both ITSS and Q were significantly lower in the treated group at each time point ( P < 0.05). Measurements in the treated group showed that ITSS persisted at 7 days ( P = 0.669) and increased at 14 and 21 days ( P < 0.05), while Q significantly declined at 7 days ( P = 0.028) and gradually increased at 14 and 21 days. In the treated group, significant correlation was found between Q and histologic microvessel density (MVD) ( r = 0.753, P < 0.001), and ITSS correlated well with MVD ( r = 0.742, P = 0.002) after excluding the data from baseline. This study demonstrated that USPIO-enhanced SWI and Q could provide novel biomarkers for evaluating antiangiogenic effects of Sorafenib on HCC.